Impact of Training Practices on Police Misconduct in Pampanga Police Provincial Office - Banatao, Maylanie C.; Castillo, Richard P.; Grospe, Zenmar O.; Pia, King Relan M.; Ricohermoso, Nelvin M.; Villa, Elizabeth B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to investigate the impact of training on police misconduct in Pampanga Police Provincial Office. It determined the following questions: (a) Impact training practices of the police officers in Pampanga Police Provincial Office in terms of the following: ethical training programs; development initiatives, recruitment strategies, and accountability measures; (b) assessment of the respondents as to police misconduct in corruption and bribery, political interference, and lack of resources; drug war policies; impunity; lack of oversight and accountability; bias and discrimination; media influence; and economic conditions; and significant relationship between the impact of training practices and assessment of the respondents as to police misconduct among police officers in Pampanga Police Provincial Office. The descriptive correlation method was employed with 775 select respondents. The results are as follows:(a) the impact of training practices among the police officers in Pampanga Police Provincial Office in terms of ethical training programs, leadership development initiatives, recruitment strategies, and accountability measures highly impactful; (b) The respondents agreed that as to police misconduct that it was highly impactful in terms of corruption and bribery. The remaining indicators have obtained an impactful interpretation. These are as follows: political interference, lack of resources, drug policies, impunity, lack of oversight and accountability, bias and discrimination, media influence, and economic conditions; (c) The impact of ethical training programs is significantly positively correlated with each measured facet of police misconduct. These suggest adequate, ethical training programs could reduce these issues within the law enforcement community. This demonstrates how vital comprehensive ethical training is for tackling all facets of police wrongdoing and enhancing the department's professionalism; (d) Every measured aspect of police misconduct exhibited a robust positive link with the effectiveness of Leadership Development Initiatives. The correlation coefficients for lack of oversight and accountability range from 0.448 (moderate positive correlation) to 0.751 (strongly positive correlation), depending on the issue. The statistical significance of the correlations is confirmed, and the null hypothesis (Ho) is rejected because the p-values for all dimensions are 0.000. This shows that respondents tend to give more positive ratings of various aspects of police misconduct as the impact of Leadership Development Initiatives on police officers improves; and (e). The respondents' assessments of police misconduct and the effects of police training practices established the statistical significance of these correlations, and the correlation coefficients showed the direction and intensity of the relationship between the two variables. Every aspect of police misconduct shows a strong positive link with the effect of recruitment strategies, which aligns with earlier research.